A review of fault diagnosis and fault-tolerant control of vehicular polymer electrolyte membrane fuel cell power system. Issue 1 (1st February 2022) - Pan, Tongyu; Zhang, Pei; Du, Changqing; Wu, Dongmei
Abstract: Proton exchange membrane fuel cell (PEMFC) is a promising vehicle power because of its high energy conversion efficiency and pollution-free reactant. However, the complex structure of multi-system coordination makes the correlation between parameters strong, the fault rate is high and the control is difficult. Timely and accurate fault diagnosis and effective fault-tolerant control are of great significance to the stable output and durability of PEMFC system. Firstly, this paper classifies different faults and describes the applicable scenarios of each classification method. Then, the fault diagnosis methods based on experiment, model and data are summarized, and their advantages and disadvantages are compared. Then, the methods and characteristics of hardware fault tolerance and software fault tolerance are analyzed from the point of redundancy, and the application of fault tolerance control in maintaining the stability of PEMFC system is summarized. Finally, the improvement direction and development prospect of fault diagnosis related technology of vehicle PEMFC system are proposed.